2011
DOI: 10.1016/j.juro.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Modified Clavien Classification in Percutaneous Nephrolithotomy: Assessment of Complications in Children

Abstract: Percutaneous nephrolithotomy in children is safe, feasible and effective. Stone burden and operative time are independent risk factors for complications. The modified Clavien system provides a straightforward and validated method to classify postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 21 publications
3
49
1
1
Order By: Relevance
“…The modified Clavien system focuses mainly on the therapeutic consequences of a complication, emphasizing the level of the required intervention. The system is generally used to report complications occurring up to 90 days postoperatively, although it can also be applied to late complications [24]. We applied this classification system to stratify the recorded complications of URS for ureteral stones with different localizations in our institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified Clavien system focuses mainly on the therapeutic consequences of a complication, emphasizing the level of the required intervention. The system is generally used to report complications occurring up to 90 days postoperatively, although it can also be applied to late complications [24]. We applied this classification system to stratify the recorded complications of URS for ureteral stones with different localizations in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study is retrospective, which may lead to an inadequate recording of minor, self-limited complications. Ozden et al [24] reported their results in children treated with percutaneous nephrolithotomy and stated that auxiliary procedures such as SWL and second-look percutaneous nephrolithotomy, which were classified as grade III complications, are not complications but rather part of the treatment strategy. When we reviewed our results, we were faced with the same issue.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kroovand [18] stated that adult-sized instruments are suitable to use in children including infants and toddles. Ozden et al [19] stated that modiWed Clavien system provides a straightforward and validated method to classify postoperative complications in pediatric PNL patients although they did not mention the type of instruments (pediatric vs. adult type) used in their evaluation. In our series, we had 15 complications and due to the modiWed Clavien system 3 were Grade I, 10 were Grade II and 2 were Grade IIIb.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative data included side of operation, location of stone, location and number of tracts, and operative time. Outcome data included SFR at discharge, length of hospital stay, need for second-look nephroscopy, occurrence of complication coded according to the Modified Clavien Classification System [18], and stone composition. SFR was defined as no residual stones !3 mm on postoperative kidney ureter bladder (KUB) radiography, ultrasound, nephrostogram, or computed tomography (CT), according to surgeon preference.…”
Section: Methodsmentioning
confidence: 99%